Herd Behaviour among Investors in Indian Stock Markets: An Evidence from Information Technology Sector - Francis, Jency; Jose, Neethu; Nair, Parvathy G. (International Journal of Psychosocial Rehabilitation, 2020)
The study aims at examining the existence of herding behavior patterns specifically in one of the sectoral index (IT) in contrast to the multi-sectoral benchmark index in an emerging economy like India. It also looks for the existence of herd behaviour in two opposite market conditions: bearish and bullish in the Indian Stock Market using Cross Sectional Absolute Deviation (CSAD) which is the absolute average of the total of the difference between the return of individual securities and the market return, as dependent variable and market return as independent variable using OLS Regression. The analysis is based on the daily closing values of S&P BSE IT index and its 30 constituents’ scripts for a period of six years ranging from April 1, 2013 to March 31, 2019 for identifying the presence of herd behaviour. The coefficients of squared market return for these selected constituent companies of S&P BSE Information Technology Index are not negative in the whole period; but negative in cases of Mphasis Ltd and Tanla Solutions Ltd in the bullish period and Tanla Solutions Ltd in the bearish period, showing no conclusive evidence of herding behaviour in the S&P BSE Information Technology Index as a whole and also herding behaviour is not prevalent in any of the market scenarios in the Indian stock market which indicates that the investors are rational in investment decisions.